THE CONFLICT OF ABAILARD AND ST BERNARD - Sikes, J. G. (The journal of theological studies, 1927)
J. G. SIKES; THE CONFLICT OF ABAILARD AND ST BERNARD, The Journal of Theological Studies, Volume os-XXVIII, Issue July, 1 July 1927, Pages 398–402, https://doi.